Srī Nānaka prakāsha : Sikkha pantha de sājanahāra Srī Gurū Nānaka Dewa niraṅkārī dā jīwana britānta - Sāhiba Siṅgha, 1894- (SAMP early 20th-century Indian books project ;)
Narrative poem on Guru Nanak, 1469-1538.